Virtual Ophthalmology Rotation for Visiting Medical Students: An Opportunity to Enhance Diversity in the Workforce - Yousuf, Salman J.; Nguyen, Nguyen S.; Oskuei, Monika Farhangi; Kwagyan, John; Jones, Leslie S. (Journal of Academic Ophthalmology, 2023)
Introduction We created a virtual rotation to facilitate the exposure of ophthalmology to medical students and serve as a pilot program to help attract students from under-represented in medicine (URM) backgrounds. In addition to the rotation eliminating the financial burdens associated with in-person away rotations, we offered a not-for-credit (i.e., drop-in) option that included sessions outside the typical clinic hours. This option reduced scheduling conflicts as a barrier to enrollment and allowed junior medical students and postgraduates to participate and hopefully further develop an interest in ophthalmology.Methods Before the rotation, participants completed a pre-test and a survey to collect data on learners' backgrounds and interest in applying for ophthalmology residency. The rotation included live lectures, case-based discussions, chart reviews, and guided self-study. Following the rotation, participants completed a post-test and a survey to query applicants on the online rotation's utility and delivery.Results Eleven learners enrolled in the course and completed the prerotation survey and test. Approximately one-third (4/11; 36%) were URM students and two-thirds (7/11; 64%) were female. All responded they were planning to apply for ophthalmology residency. All responded they strongly agreed that the rotation increased their general knowledge in ophthalmology, and 89% (9/11) strongly agreed that it improved their ability to diagnose and manage actual patients. Nearly all (7/8; 87.5%) strongly agreed the rotation provided the opportunity to seek support for the residency application process, and all found the online platform reliable and easy to access. Exam scores improved significantly from pre- to post-tests (60 vs. 79%; p < 0.01).Conclusions The rotation attracted a substantial proportion of URM students. Learners reported that the virtual rotation effectively taught and supported their endeavors to become ophthalmologists. Virtual rotations for visiting students can reduce barriers such as travel, financial costs, and time constraints that might otherwise hinder exposure to specialty training that is not offered or is underrepresented at students' home institutions. Increasing exposure and offering mentorship through this novel platform deserves further study to enhance diversity and inclusion in medicine.
Keywords: COVID-19; virtual education; diversity; ophthalmology; medical education; under-represented